The influence of consumer protection on the satisfaction of airline passengers - Neacşu Nicoleta Andreea (Proceedings of the International Conference on Business Excellence, 2019)
In a society in continuous development, air transport is no longer a luxury, but a means of transportation for everyone. As a result of rising living standards, reducing the cost of air travel compared to other means of transport, more and more people prefer to travel by air even at short distances. The steady increase in popularity and accessibility of air transport has led, in some cases to a decrease in the quality of services provided by air transport companies and in violation of consumer rights. The evolution of consumer protection has influenced positively the quality of air transport services by imposing certain obligations and offering a very high level of security, which increases passenger satisfaction. This article aims to quantify the passanger satisfaction and how the rights and interests of travelers in Romania are protected. In this respect, the authors carried out a quantitative research done among consumers of air transport services. Through a quantitative exploratory empirical research, 110 people were interviewed. The results obtained have made it possible to determine the extent to which the airline they have called upon, succeeds in meeting their expectations and satisfying them, and their rights have been respected. At the same time, passengers’ perception of the quality of air services were also quantified. Based on the results, the authors make some recommendations to airline companies’ management: to develop effective strategies to protect the rights and interests of travelers, to permanently identify the needs of the actual customers.